Funkcje Naprężeń w Teorii Powłok Siatkowych - Bojda, K.H. (Engineering Transactions, 1973)
In the paper are considered the stress functions used in the theory of surface lattice structures, which may be modelled by a two-dimensional, fibrous Cosserat medium. Stress functions of the non-polar shell theory are discussed in particular, i.e., in the theory of surface trusses and lattice plates. The relations derived may be used in solving the problems (formulated in stresses) of statics of lattice surface structure.